Design and Construction of Crimping Press Equipment Perfume Bottle Sprayer (Crimper) - Mulyadi; Asmed; Permana, Dirga; Nuhu Kankia, Mukhtar; Leni, Desmarita (IJIMCE : International Journal of Innovation in Mechanical Construction and Energy, 2024)
This research examines the Perfume Bottle Sprayer Crimping Press Tool (Crimper), designed to install the sprayer on perfume bottles using the principle of a simple lever-type device. The focus of the research was to evaluate the reliability of the tool in preventing leaks at various heights of perfume bottles. The Crimper manufacturing process includes using a milling machine to form flat sides, cutting with a grinder for precise dimensions, and welding using a TIG welding machine with argon gas to maintain the strength of the stainless steel. Tests carried out on perfume bottles with heights of 95 mm, 68 mm and 71 mm, showed that the Crimper was successful in preventing leaks in all tests. The results confirm the reliability and efficiency of tools in industry, in line with the demands of an increasingly competitive global market. Thus, Crimper not only meets technical specifications but can also be relied on to increase production efficiency and maintain consistent product quality.